Trimodality therapy with salvage focal brachytherapy for seminal vesicle recurrence after prostate cancer brachytherapy - Makoto Nakiri; Hirofumi Kurose; Shinnosuke Komine; Hiroki Suekane; Katsuaki Chikui; Kosuke Ueda; Keiichiro Uemura; Kiyoaki Nishihara; Koichiro Muraki; Chikayuki Hattori; Etsuyo Ogo; Tsukasa Igawa (Urology Case Reports)
Salvage therapy is effective for treating local recurrence following radiation therapy for prostate cancer. Although surgery, radiation therapy, and hormonal therapy can be considered as options for salvage therapy for seminal vesicle recurrence of prostate cancer, there are reports of poor outcomes, and many cases involve treatment difficulties and post-treatment recurrence. In this article, we report our findings on the use of trimodality therapy, consisting of salvage focal brachytherapy, intensity-modulated radiation therapy, and hormonal therapy, in a patient who showed seminal vesicle recurrence 10 years after brachytherapy, with no major adverse events and no biochemical recurrence over 5 years.